Legal Review of Bullying or Bullying Behavior in Indonesia - Agus Sugiarto (Jurnal Restorasi : Hukum dan Politik, 2024)
Bullying or bullying behavior is a social problem that is increasingly disturbing in various levels of society, including in Indonesia. Bullying is an action taken by someone to attack someone not only physically but also psychologically. The development of the times makes it easier for people to interact, so that people, especially students, can easily carry out bullying, most of which is caused by promiscuity, lack of parental attention and a free environment. This research aims to conduct a legal review of bullying behavior in the context of Indonesian law. The research method used is normative legal research with literature study by collecting data from various sources related to statutory regulations, court decisions, as well as legal and psychological literature. The results of the research show that based on the Child Protection Law, acts of bullying in the school environment are included as criminal acts of violence against children. Article 76C of the Law explains the prohibition against anyone committing violence against children. If this rule is violated, the perpetrator can be subject to sanctions in accordance with Article 80 of Law 35/2014, which can include imprisonment and a fine. For offenders under the age of 18, the Juvenile Criminal Justice System Law provides an approach that takes into account the best interests of the child, by prioritizing restorative justice and diversion as an alternative to the formal justice process. Apart from that, the SPPA Law also stipulates various measures that can be imposed on child perpetrators, including basic and additional penalties aimed at their recovery and social reintegration. Schools also have a legal obligation to protect their students from acts of violence, by implementing anti-bullying policies, raising awareness, and providing protection for victims. Thus, the regulations in the Child Protection Law and the SPPA Law emphasize the importance of protecting children from bullying in the school environment and handling cases with an approach that takes into account the child's best interests.